Molecular basis for fibrinogen Dusart (A alpha 554 Arg-->Cys) and its association with abnormal fibrin polymerization and thrombophilia. - Koopman, J (1993)
The molecular defect in the abnormal fibrinogen Dusart (Paris V) that is associated with thrombophilia was determined by sequence analysis of genomic DNA that had been amplified using the polymerase chain reaction. The propositus was heterozygous for a single base change (C-->T) in the A alpha-chain gene, resulting in the amino acid substitution A alpha 554 Arg-->Cys. Restriction analysis of the amplified DNA derived from the family members showed that his father and his two sons were also heterozygous. Electron microscopic studies on fibrin formed from purified fibrinogen Dusart demonstrated fibers that were much thinner than in normal fibrin. In contrast to the previously observed defective binding of plasminogen, the binding of thrombospondin to immobilized fibrinogen Dusart was similar to that of normal fibrinogen. Immunoblot analysis of plasma fibrinogen demonstrated that a substantial part of the fibrinogen Dusart molecules were disulfide-linked to albumin. The plasma of the affected family members also contained fibrinogen-albumin complexes. Furthermore, small amounts of high molecular weight complexes containing fibrinogen were detected in all the heterozygous individuals. These data indicate that the molecular abnormality in fibrinogen Dusart (A alpha 554 Arg-->Cys) results in defective lateral association of the fibrin fibers and disulfide-linked complex formation with albumin, and is associated with a family history of recurrent thrombosis in the affected individuals.